TECHNOLOGY AND INTERNATIONAL RELATIONS: CRISIS OR OPPORTUNITY? - ERCAN, Arda (SSD Journal, 2020)
The traditional concept of international relations, which built with the Westphalia treaty of 1648, has undergone a great change after half a century. nternational relations, dominated by states and maintained by traditional methods, have been replaced by an international relations where individuals can become actors and diplomacy and relations are transferred to the virtual environment. This new era in which cloud borders are set and artificial intelligence is involved in the decision-making mechanism brings along a series of threats and opportunities for states. In this study, while discussing the opportunities of the state with increased communication skills, it is also evaluated how the importance given by realism to the state disappears.